Current Updates on Oxazolidinone and Its Significance. (22nd February 2012) - Pandit, Neha; Singla, Rajeev K.; Shrivastava, Birendra
Abstract : Oxazolidinone is a five-member heterocyclic ring exhibiting potential medicinal properties with preferential antibacterial activity. Scientists reported various synthetic procedures for this heterocyclic structure. Current review articles tried to cover each and every potential aspect of oxazolidinone like synthetic routes, pharmacological mechanism of action, medicinal properties, and current research activities.